PERLINDUNGAN KEDUDUKAN AHLI WARIS PENDERITA CACAT MENTAL DALAM PEMBAGIAN HARTA WARISAN (Perspektif KUH Perdata) - Arya Adi Bintoro; Ambar Budhisulistyawati (Jurnal Privat Law, 2026)
This article examines the position and rights as well as distribute inheritance to heirs with mental disabilities according to the perspective of the Civil Code. This type of research is normative with the nature of prescriptive legal research. Based on the provisions of the Civil Code, people with mental disabilities remain entitled and have the position of heirs of people with mental disabilities over the distribution of inheritance through a curatele by an expert curator to support the heirs of people with mental disabilities to continue to get their inheritance rights. With regard to this problem, it is necessary to reform and improve the special rules of the Civil Code regarding the position and rights of heirs with mental disabilities in the distribution of inheritance.